Effect of suppressive acyclovir administered to HSV-2 positive mothers from week 28 to 36 weeks of pregnancy on adverse obstetric outcomes: a double-blind randomized placebo-controlled trial - Nakubulwa, Sarah; Kaye, Dan K.; Bwanga, Freddie; Mbona Tumwesigye, Nazarius; Nakku-Joloba, Edith; Mirembe, Florence (Reproductive health, 2017)
Acyclovir (ACV) given to HSV-2 positive women after 36 weeks reduces adverse outcomes but its benefit at lower gestation was undocumented. We determined the effect of oral acyclovir administered from 28 to 36 weeks on premature rupture of membranes (PROM) primarily and preterm delivery risk. This was a randomized, double-blind placebo-controlled trial among 200 HSV-2 positive pregnant women at 28 weeks of gestation at Mulago Hospital, Uganda. Participants were assigned randomly (1:1) to take either acyclovir 400 mg orally twice daily (intervention) or placebo (control) from 28 to 36 weeks. Both arms received acyclovir after 36 weeks until delivery. Development of Pre-PROM by 36 weeks and preterm delivery were outcomes. One hundred women were randomized to acyclovir and 100 to placebo arms between January 2014 and February 2015. There was tendency towards reduction of incidence of PROM at 36 weeks but this was not statistically significant (4.0% versus 10.0%; RR 0.35; 95% 0.11–1.10) in the acyclovir and placebo arms respectively. However, there was a significant reduction in the incidence of preterm delivery (11.1% versus 23.5%; RR 0.41; 95% 0.20–0.85) in the acyclovir and placebo arms respectively. Oral acyclovir given to HSV-2 positive pregnant women from 28 to 36 weeks reduced incidence of preterm delivery but did not significantly reduce incidence of pre-PROM.
Keywords: Acyclovir; Herpes simplex type 2; Genital herpes; Adverse obstetric outcomes; Pregnancy; Randomized controlled trial; Uganda